Politics and State-building in the Solomon Islands - Dinnen, Sinclair (ANU Press, 2008)
Politics and State Building in Solomon Islands examines a crisis moment in recent Solomon Islands history. Contributors examine what happened when unrest engulfed the capital of the small Melanesian country in the aftermath of the 2006 national elections, and consider what these events show about the Solomon Islands political system, the influence of Asian interests in business and politics, and why the crisis is best understood in the context of the country's volatile blend of traditional and modern politics. Until the disturbances of April 2006 and subsequent deterioration in bilateral relations between Australia and Solomon Islands under the Sogavare government, experts had hailed the Regional Assistance Mission to Solomon Islands (RAMSI) as an unqualified success. Some saw it as a model for 'cooperative intervention' in 'failing states' worldwide. Following these developments success seems less certain and aspects of the RAMSI model appear flawed. Using the case of Solomon Islands, this book raises fundamental questions about the nature of 'cooperative intervention' as a vehicle for state building, asking whether it should be construed as a mainly technical endeavour or whether it is unavoidably a political undertaking with political consequences. Providing a critical but balanced analysis, Politics and State Building in Solomon Islands has important implications for the wider debate about international state-building interventions in 'failed' and 'failing' states.